Pengaruh Efektivitas PAD, Kemandirian Keuangan Daerah, Belanja Modal dan Ukuran Pemerintah Daerah Terhadap Kinerja Keuangan Provinsi Papua Pegunungan - Diana Togu Sihotang; J.Ary Mollet; Halomoan Hutajulu (Indonesian Journal of Public Administration Review, 2025)
This study was conducted to assess the relationship between the effectiveness of Regional Original Revenue (PAD), the level of regional financial independence, capital expenditure, and the size of local governments on financial performance in districts in Papua Mountainous Province during the 2017–2023 period. All data used came from the APBD realization report published by the Directorate General of Fiscal Balance of the Ministry of Finance.A quantitative approach with a descriptive-verifiable method was applied in the analysis, with the use of multiple linear regression supported by classical assumption tests and statistical tests t and F statistical tests to measure the strength of influence of each variable. The results obtained show that the effectiveness of PAD and the size of local governments have not been proven to affect the financial performance of local governments. On the other hand, the level of regional financial independence and capital expenditure make a significant contribution in encouraging changes in the financial performance of each local government. These findings show that the fiscal ability of regions to finance needs independently and the amount of regional investment through capital expenditure are more decisive factors in improving financial performance than the amount of PAD and the organizational scale of local governments.